Gender-based violence screening methods preferred by women visiting a public hospital in Pune, India - Nishi Suryavanshi; Shilpa Naik; Smita Waghmare; Nikhil Gupte; Sameer Khan; Vidya Mave; Andrea Deluca; Amita Gupta; Jonathan Golub; Robert C. Bollinger; Anita Shankar (BMC, 2018)
Abstract Background Gender-based violence (GBV) is a major global public health concern and is a risk factor for adverse health outcomes. Early identification of GBV is crucial for improved health outcomes. Interactions with health care providers may provide a unique opportunity for routine GBV screening, if a safe, confidential environment can be established. Methods Between November 2014 and February 2015, a cross-sectional, observational study was conducted where women were interviewed about their opinions concerning GBV screening in a tertiary health care setting in Pune, India. Trained counsellors interviewed 300 women at different out-patient and in-patient departments using a semi-structured questionnaire. Results Twenty-three percent of these women reported experiencing GBV in their life. However, 90% of women said they had never been asked about GBV in a health care setting. Seventy-two percent expressed willingness to be asked about GBV by their health care providers, with the preferred provider being nurses or counsellors. More than half (53%) women reported face-to-face interview as the most preferred method for screening. There were no major differences in these preferences by GBV history status. Conclusions Our study provides evidence for preferred GBV screening methods and optimal provider engagement as perceived by women attending a public hospital.